Decreased HIV-associated mortality rates during scale-up of antiretroviral therapy, 2011–2016. (1st December 2019) - Otieno, George; Whiteside, Yohance Omar; Achia, Thomas; Kwaro, Daniel; Zielinski-Gutierrez, Emily; Ojoo, Sylvia; Sewe, Maquins; Musingila, Paul; Akelo, Victor; Obor, David; Nyaguara, Amek; De Cock, Kevin M.; et al.
Abstract : Objective: HIV-associated mortality rates in Africa decreased by 10–20% annually in 2003–2011, after the introduction of antiretroviral therapy (ART). We sought to document HIV-associated mortality rates in the general population in Kenya after 2011 in an era of expanded access to ART. Design: We obtained data on mortality rates and migration from a health and demographic surveillance system (HDSS) in Gem, western Kenya, and data for HDSS residents aged 15–64 years from home-based HIV counseling and testing (HBCT) rounds in 2011, 2012, 2013, and 2016. Methods: Mortality trends were determined among a closed cohort of residents who participated in at least the 2011 round of HBCT. Results: Of 32 467 eligible HDSS residents, 22 688 (70%) participated in the 2011 round and comprised the study cohort. All-cause mortality rates declined from 10.0 [95% confidence interval (CI) 8.4–11.7] per 1000 in 2011 to 7.4 (95% CI 5·7–9·0) in 2016, whereas the mortality rate was stable among HIV-uninfected residents, at 5.7 per 1000 person-years. Among HIV-infected residents, mortality rates declined from 30.5 per 1000 in 2011 to 15.9 per 1000 in 2016 (average decline 6% per year). The HIV-infected group receiving ART had higher mortality rates than the HIV-uninfected group [adjusted rate ratio (aRR) 2.8, 95% CI 2.2–3.4], as did the HIV-infected group who did not receive ART (aRR 5.3, 95% CI 4.5–6.2). Conclusions: Mortality rates among HIV-infected individuals declined substantially during ART expansion between 2011 and 2016, though less than during early ART introduction. Mortality trends among HIV-infected populations are critical to understanding epidemic dynamics.